Chemistry of pyrroles - Trofimov, B. A. (Boris Aleksandrovich) (CRC Press, 2015)
During the last 30 years, knowledge of the essential role that pyrrole structures play in the chemistry of living organisms, drug design, and the development of advanced materials has increased. Correspondingly, research on the diverse issues of synthetic, theoretical, and applied chemistry has snowballed. Devoted to the latest achievements of this field, Chemistry of Pyrroles covers the discovery and development of a novel, facile, and highly effective method for the construction of the pyrrole ring from ketones (ketoximes) and acetylene in superbase catalytic systems (Trofimov reaction). It.